Moss species diversity in the glacial cirques of the Polish Karkonosze Mts. and its changes during the 20th century - Fudali, Ewa (Biodiversity: Research and Conservation, 2013)
Bryo-floristic data from the 19th century and the first decade of the 21th century were compiled and compared to find trends in moss flora transformations during the analysed period. The total number of moss species reported from the glacial cirques in the Polish part of the Karkonosze Mts. amounted to 229 (230 taxa) and the comparison showed 49% of species replaced; 68 taxa were not refound and 45 were reported for the first time. But it seems highly probable that a great number of “newcomers” occurred only in the past and were omitted or overlooked by the 19th century researchers. 23 species among those persistent during the 20th century were found presently in no more than half of the previous localities, so they seem to demand care as probably threatened. Full list of taxa recorded from the individual objects in the studied period, including results of herbarium specimen revision, is provided.